Experience of dolutegravir-based antiretroviral treatment and risks of diabetes mellitus. (February 2022) - Hirigo, Agete Tadewos; Gutema, Selamawit; Eifa, Aberash; Ketema, Worku
HIV-infected people have started to live longer since the introduction of antiretroviral therapy, however various co-morbid illnesses have emerged. Three HIV-infected individuals, all at least 43 years old, reported with a new onset of type 2 diabetes after switching to dolutegravir-combined antiretroviral therapy regimen. These three people were switched to integrase strand transfer inhibitor (dolutegravir)-based first-line antiretroviral treatment after receiving non-nucleoside reverse transcriptase inhibitor-combined first-line antiretroviral treatment for at least 6 years, as recommended by the World Health Organization for Sub-Saharan African countries, including Ethiopia.All of the given cases had normal plasma fasting sugar (fasting blood sugar <100 mg/dL) at the time of switching. Polyuria, polydipsia, considerable weight loss, and fatigue were all classified as signs of diabetes mellitus in the two male cases. In addition, their laboratory results demonstrated hyperglycemia (plasma fasting blood sugar > 200 mg/dL and urine glucose level ⩾2+) with no ketonuria after switching to dolutegravir for 4–10 months. A glycemic control was achieved, and metformin medication was continued. After 6 months of dolutegravir treatment, the third female case developed diabetic ketoacidosis and severe hyperglycemia (fasting blood glucose level 600 mg/dL, urine glucose level 3+, and ketonuria 3+). To recover from diabetic ketoacidosis, the patient was given intravenous normal saline and regular insulin. Her glycemic control was then restored, and she was switched to NPH insulin. For all of the cases presented, the dolutegravir-based regimen was maintained. Antiretroviral regimens using dolutegravir have the potential to cause hyperglycemia and other side effects. As a result, blood glucose monitoring is required throughout treatment initiation and regularly throughout treatment follow-up, particularly for those on dolutegravir-combined antiretroviral therapy regimens.